Trends in Lightweight Automotive Materials for Improving Fuel Efficiency and Reducing Carbon Emissions - Gunawan Refiadi; Iis Siti Aisyah; Januar Parlaungan Siregar (Automotive Experiences, 2019)
Depletion of fossil fuels and greenhouse gases is an essential issue in the development of the automotive industry. From the design stage, material selection becomes the most crucial factor. Therefore, this article discusses the development of lightweight automotive materials for increasing fuel efficiency and reducing carbon emissions. Material reliability is assessed by how much weight reduction can be achieved, production costs, safety and durability. Ferro materials (mild steel, High Strength Steel, and Advanced High Strength Steel), non-ferrous (aluminium and magnesium alloy), and Fiber Reinforced Plastics (FRP) have been proven to reduce the total weight of vehicles up to 12.6%. Confirmation of statistical data from the literature illustrates the possibility of using lightweight material to achieve zero CO2 emission. In addition, the 12.6% weight reduction still meets the vehicle safety factor.